PENGARUH KUALITAS PRODUK, PERSEPSI KEAMANAN DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN PADA MERCHANT DI TIKTOK: Indonesia - Vivi, Vivi; Hikmah, Hikmah (LPPM Universitas Putera Batam, 2025)
This study investigates the influence of product quality, security perception, and trust on consumer purchasing decisions toward merchants on TikTok Shop. With the rapid growth of social commerce in Indonesia, TikTok Shop has emerged as a popular platform for purchasing beauty products. As an illustrative case, this research highlights Scarlet a well known local skincare brand to understand consumer behavior in this digital marketplace. Utilizing a quantitative approach, data were collected from 204 respondents through online questionnaires with Likert scale measurements. The study employed purposive sampling and applied multiple linear regression analysis to assess the relationships among variables. The findings demonstrate that product quality, security perception, and trust each exert a positive and significant effect on purchasing decisions. These results provide important implications for TikTok merchants in enhancing their marketing strategies by maintaining product quality, strengthening trust, and ensuring perceived transaction security to increase consumer purchase intentions.